Unveiling the drivers of collaborative entrepreneurship and its role in value co-creation - Saleh Al-Omoush , Khaled; Odriozola-Fernandez, Ignacio; Ribeiro-Navarrete, Samuel (Transformations In Business & Economics, 2026)
This study explores the environment of collaborative entrepreneurship in terms of its determinants and outcomes. Data were collected from 204 managers and specialists in renewable energy companies, and was analysed with Smart PLS. The results revealed that market dynamism and collaborative orientations significantly impact the perpetration of collaborative entrepreneurship. The study also found that relationship quality plays a vital mediating role in the impact of collaborative orientation on collaborative entrepreneurship. In addition, collaborative entrepreneurship was found to have a significant impact on value co-creation. The findings of this study enhance our understanding of the collaborative entrepreneurship environment, the mechanisms of its implementation, and how to measure its performance. It also enriches the knowledge of companies and experts interested in achieving collaborative entrepreneurship to deal with challenges and the accompanying opportunities that arise with market dynamism that are difficult to exploit individually.
Keywords: collaborative entrepreneurship; market dynamism; collaborative orientations; relationship quality; value co-creation; renewable energy companies